Newly diagnosed non‐small cell lung cancer with interstitial lung abnormality: Prevalence, characteristics, and prognosis - Min Zhu; Jiawen Yi; Yanping Su; Yixiao Zhang; Yanli Gao; Xiaoli Xu; Shu Zhang; Yuhui Zhang; Kewu Huang (Thoracic Cancer, 2023)
Abstract Background Along with the improvement of lung cancer screening implementation, the identification of interstitial lung abnormality (ILA) is increasing. Currently, there is a limited description of the oncogenic status and ILA subtypes among newly diagnosed non‐small cell lung cancer (NSCLC) patients with ILA in the Chinese population. This study aimed to investigate the prevalence, characteristics, oncogenic status and factors associated with overall survival (OS) among NSCLC patients with ILA. Methods A total of 765 newly diagnosed NSCLC cases at our hospital were reviewed and ILA was diagnosed according to the criteria of the Fleischner Society. The characteristics, clinical pathological features and OS of NSCLC patients with ILA were retrospectively analyzed. Results Of the 765 patients included in the study, 101 (13.2%) cases experienced ILA at the time of NSCLC diagnosis. Multivariate analysis revealed that ILA was more likely to be detected in NSCLC patients who were age ≥60 (OR 2.404, p = 0.001), male gender (OR 2.476, p = 0.004), and EGFR wild‐type (OR 2.035, p = 0.007). Additionally, according to the multivariate Cox model, the presence of ILA in NSCLC patients was significantly associated with a shorter OS period than those without ILA (751 days vs. 445 days, HR 0.6, p = 0.001). Following analysis, it was determined that OS in patients with usual interstitial pneumonia (UIP) was shorter than in those without UIP (HR 1.82, p = 0.037). Conclusion ILA is a common comorbidity among newly diagnosed NSCLC patients. We found that patients with EGFR wild‐type NSCLC were more likely to develop ILA. The presence of ILA, especially UIP, was significantly associated with poor NSCLC prognosis.